Looming changes in the management of “osteoporosis”: A preview for clinicians - Frost, H. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Normally, strong muscles make strong load-bearing bones, and persistently weak muscles make weak ones. We now have a general understanding of how and why that happens. Unexpectedly that understanding also affects our understanding of the nature, pathogenesis and study of disorders currently classified as “osteopaenias” and “osteoporoses”. Such things promise to change how we view, study and manage those disorders. At present, those things incite discussions among authorities that in time should lead to a new accepted “wisdom” about those disorders. Many clinicians who manage patients on a daily basis would probably like to know what issues that process concerns. Because of the importance of those issues to so many millions of this planet's present and future six billion souls, and because of their bearing on the related research, one could argue that clinicians and researchers are entitled to know about those issues. For that reason this article summarizes some of them, of course as I seem them.It is understood that other times, places and people would resolve any questions about those issues, and that any new accepted wisdom that depends upon their resolution should lie in the future.Recent recognition of the effects of muscle and biomechanics on the biologic ‘‘machinery” that determines whole-bone strength and bone health incite many changes in formerly accepted views about the nature, diagnosis, pathogenesis, study and management of the group of different disorders that are currently considered as falling under the umbrellas of “osteoporosis” and “osteopaenia”. This article acquaints interested physicians with some of those changes and the reasons for them. It should take time, probably several years, for those changes to gel into an accepted new standard of care for such disorders. Meanwhile currently accepted standards of care could and probably should be followed.
Keywords: Treatment; absorptiometry; biomechanics; diagnosis